The unexpected diversity in Amphora sensu lato (Bacillariophyta) at Sozopol Bay, the western Black Sea - Zidarova, Ralitsa; Ivanov, Plamen; Hristova, Ognyana; Dzhurova, Boryana; Hineva, Elitsa (Phytotaxa, 2022)
During a survey of benthic diatoms from the Bulgarian Black Sea coast near the historic town of Sozopol, we found a high diversity of Amphora sensu lato taxa at a single site and on a single type of artificial substratum. A total of 40 taxa from the current genera Amphora, Halamphora, Seminavis and Tetramphora were recognized during light microscopy (LM) and scanning electron microscopy (SEM) observations. We were able to identify with a high degree of certainty only 6 taxa based on the literature, whereas for 19 taxa (or almost 50% of all taxa) we could not find even sufficiently similar species, and they remained unidentified to species level. Many of the species had small valve dimensions. The paper presents all taxa with short morphometric data and microphotographs under LM and SEM, where possible. All taxa are discussed and compared with similar known taxa. The illustrative materials in earlier works from the Black Sea and species descriptions, where such were available, were also consulted. Diversity of Amphora sensu lato in the Black Sea coastal waters seems to be underestimated, whereas some of the past records are uncertain. A discussion on the current state of knowledge of Amphora sensu lato species from the Black Sea is given.